1982
DOI: 10.1136/thx.37.9.646
|View full text |Cite
|
Sign up to set email alerts
|

Sputum and ciliary inhibition in asthma.

Abstract: Twenty-eight sputum samples collected from 20 patients with chronic bronchial asthma of atopic and intrinsic clinical types were incubated with human bronchial explants to study their influence on ciliary motility. Of these, 19 (68%) of the sputa exerted a ciliary inhibitory effect of varying degree in a two-hour period. Analysis of the data indicates that (1) the ciliary inhibitory effect was invariably present when patients produced a distinctive slurry sputum; (2) this occurred more frequently during clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The marked reduction in ciliary beat frequency and abnormal beat pattern seen in asthmatic airway epithelium, particularly in those with severe disease, is likely to be multifactorial in causation. Evidence from previous studies 27,28 suggests that sputum from patients with asthma and products of inflammatory cells such as eosinophil major basic protein possess ciliostatic activity. Environmental factors such as exposure to irritants or chronic infection may cause secondary ultrastructural defects of the cilia that may affect the ciliary beat frequency, as indicated in a number of reports.…”
Section: Discussionmentioning
confidence: 98%
“…The marked reduction in ciliary beat frequency and abnormal beat pattern seen in asthmatic airway epithelium, particularly in those with severe disease, is likely to be multifactorial in causation. Evidence from previous studies 27,28 suggests that sputum from patients with asthma and products of inflammatory cells such as eosinophil major basic protein possess ciliostatic activity. Environmental factors such as exposure to irritants or chronic infection may cause secondary ultrastructural defects of the cilia that may affect the ciliary beat frequency, as indicated in a number of reports.…”
Section: Discussionmentioning
confidence: 98%
“…Application of Sputum from asthma patients to frogs’ isolated palates to determine the effect on CBF resulted in ciliostasis which disappeared with clinical improvement [139,140]. In comparison, samples obtained from normal volunteers and from most patients, excluding those with asthma, had no effect on ciliary beating.…”
Section: Factors That Can Affect Cbf In Asthmamentioning
confidence: 99%
“…The inhibitory effect on CBF was independent of medications used and was shown in atopic and intrinsic types of asthmatic patients. In addition, the effect was not pH dependent or related to the degree of eosinophilia [140]. Additionally, tracheal mucus velocity (TMV) was significantly less (6.3 ± 2.3 mm per min, mean ± SD, n = 6) in asymptomatic asthmatic patients than in normal subjects (11.6 ± 3.6 mm per min, n = 7) [141], and tracheal mucociliary transport rates were decreased in patients with allergic asthma [142,143].…”
Section: Factors That Can Affect Cbf In Asthmamentioning
confidence: 99%
“…16 Indeed, a recent study has demonstrated that sputum obtained from patients with asthma impairs ciliary activity in vitro. 17…”
Section: Biochemical Compositionmentioning
confidence: 99%